Efectividad de un progroma educativo en el nivel de conocimiento sobre alimentación complementaria Chepén - Villanueva Calderón, María Amada (2015)
This study is pre experimental, was conducted at Pacanguilla Health Center, Province of Chepen, during the months of October to December 2014 , in order to determine the effectiveness of the educational program "Helping my baby to grow up " on the level of maternal knowledge on complementary feeding of infants under 1 year . The sample consisted of 30 mothers who met the inclusion criteria mentioned in the investigation. The instrument used for data collection : Questionnaire to determine the level of knowledge about Complementary Feeding ( CPDNCSAC ), being the information obtained processed and analyzed by the statistical test "student’s t-test" for related samples ; the results are presented in one and double entry tables in numerical and percentage terms . After the analysis ,it was reached the following conclusions : Before application of the educational program, results show 70.0 percent of mothers scored an average level of knowledge; 6.7 percent of mothers got a low level of knowledge and 23.3 percent a higher level of knowledge. After application of the educational program, in the Post test, 100.0 percent of mothers reached a higher level of knowledge. When comparing the numbers, we can reject the null hypothesis ; the educational program was effective because it improved the maternal knowledge level to 100 percent on Complementary Feeding .